2015
DOI: 10.1890/es14-00251.1
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for constructing allometric models for the prediction of woody biomass: How many individuals to harvest?

Abstract: Abstract. The recent development of biomass markets and carbon trading has led to increasing interest in obtaining accurate estimates of woody biomass production. Aboveground woody biomass (B) is often estimated indirectly using allometric models, where representative individuals are harvested and weighed, and regression analyses used to generalise the relationship between individual mass and more readily measured non-destructive attributes such as plant height and stem diameter (D). To satisfy regulatory requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 28 publications
1
82
1
1
Order By: Relevance
“…The number of trees considered in each equation varied considerably, from as few as five trees [26] to over 100 trees [22,23]. Roxburgh et al [53] suggested that for allometric equations constructed using an adequate size-class distribution of DBH in the population, a minimum sample size of 55 trees for generic Eucalypt species was required. However, this was based on typically younger trees with a smaller DBH range than found in more mature forests-it is expected that the minimum sample size for mature native forest trees to be higher, as they are less uniform and more likely to be impacted by decay.…”
Section: Discussionmentioning
confidence: 99%
“…The number of trees considered in each equation varied considerably, from as few as five trees [26] to over 100 trees [22,23]. Roxburgh et al [53] suggested that for allometric equations constructed using an adequate size-class distribution of DBH in the population, a minimum sample size of 55 trees for generic Eucalypt species was required. However, this was based on typically younger trees with a smaller DBH range than found in more mature forests-it is expected that the minimum sample size for mature native forest trees to be higher, as they are less uniform and more likely to be impacted by decay.…”
Section: Discussionmentioning
confidence: 99%
“…Where appropriate, normality was tested with a Shapiro-Wilk test. It is common practice to use allometric biomass equations as a cost effective and efficient method of relating an easily measurable parameter to that of a less obtainable dependent factor such as dry tree weight, or total bark weight (Parresol 1999;Zianis et al 2005;Picard et al 2012;Morhart et al 2013;Roxburgh et al 2015;Cifuentes Jara et al 2015). The biomass models used within this study follow the form given in Eq.…”
Section: Discussionmentioning
confidence: 99%
“…This is common practice within biomass estimation procedures to allow for full statistical scrutiny of the data (Sprugel 1983). The log transformation of data on both x and y axis renders a linear relationship thus denoting the correct fitment of an allometric power model (Picard et al 2012;Morhart et al 2013) and also corrects data for heteroscedasticity (Zeng and Tang 2011;Roxburgh et al 2015), which is typical for biomass data (Parrasol 1999). The R package: systemfit was used for the regression analysis (Henningsen and Hamann 2007) seemingly unrelated regression (SUR) analysis was applied to ensure the additivity of the calculated biomass equations (Parresol 1999(Parresol , 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results and conclusions based on regression analysis are only reliable if these assumptions are met (Ritz and Streibig 2008;Zuur et al 2009). For biological data, however, such assumptions may be difficult to meet.…”
Section: Nonlinear Mixed Effects Modelsmentioning
confidence: 99%